TRANSFORMING SOCIAL BEHAVIOR THROUGH OPTIMIZING STUDENT MANAGEMENT IN THE SCHOOL ENVIRONMENT - Azizah, Ina; Nurfuadi, (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2025)
This research aims to analyze the influence of student management on students' social behavior in schools. Student management encompasses various techniques and strategies implemented by educators to create a learning environment that supports positive social interactions. The research method utilized is library research, gathering information from various relevant books, journals, and scientific articles. Additionally, the study incorporates survey data involving 180 elementary school students to measure aspects of cooperation, empathy, and group participation. The analysis results indicate a significant positive relationship between effective student management and the improvement of students' social behavior. The implementation of good management is proven to enhance the quality of social interactions and shape students' character to be more conducive to the learning process. These findings suggest that student management serves as a vehicle for students to develop themselves optimally in individual, social, and academic dimensions. Consequently, the study recommends that schools continue to develop management practices focused on strengthening interpersonal relationships. Optimizing synergy between teachers, parents, and the community is the primary key to realizing students who are not only academically excellent but also possess high social integrity.